Sosialisasi penanganan stunting melalui program satu kelor untuk rumah anda (SAKURA) - Nuryani, Dina Dwi; Mawardi, Qholik; Mahendra, M. Reza; Sundari, Sundari; Tambunan, Bella Aldamar; Dwiyanti, Dea Okta; Pasha, Ketut Indah Ayu (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: The moringa plant (Moringa oleifera) is widely known for its numerous health, nutritional, and economic benefits. Its leaves contain various essential nutrients, such as vitamin A, vitamin C, calcium, iron, and high levels of antioxidants, which play a vital role in preventing malnutrition, boosting immunity, and supporting family health. Through the